Intercultural education of the quechua language in the students of a public educational institution - Cárdenas-Crisóstomo, Olinda (2021)
The present study includes the analysis of the level of interculturality of the Quechua language in students and teachers of the Integrated Educational Center No. 32754 of the Centro Poblado de Ancomarca, district of Molino and province of Pachitea; which has made it possible to know in situ the indicators and intercultural competencies of the Quechua language in the study population (students and teachers). The research carried out was of a non-experimental quantitative type, using a descriptive transectional design, which received the collection of data, through the use of surveys directed to students (98), and teachers (15). The results show that the level of intercultural education of the Quechua language in the students was: 51.02% with a good level, 34.69% with a very good level, and 14.29% with a regular level; the level of intercultural education of the Quechua language in the teachers were: 73.33% with a good level, 20.00% with a very good level, and 6.67% with a regular level; and the level of intercultural education of the Quechua language in the educational center (students and teachers) were: 53.99% with a good level, 32.74% with a very good level, and 13.27% with a regular level. Conclusions: It was determined that the level of intercultural education of the Quechua language in the students corresponds to the good and very good level; the level of development of intercultural skills of the Quechua language in the students corresponds to the good and very good level; The level of development of intercultural skills of the Quechua language in teachers corresponds to the very good and good level, and the level of development of intercultural education of the Quechua language in the institution and educational study corresponds to the good and very good level.